2004
DOI: 10.1111/j.1365-313x.2003.01987.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest tent caterpillars (Malacosoma disstria) induce local and systemic diurnal emissions of terpenoid volatiles in hybrid poplar (Populus trichocarpa × deltoides): cDNA cloning, functional characterization, and patterns of gene expression of (−)‐germacrene D synthase, PtdTPS1

Abstract: These authors contributed equally to this work. SummaryFeeding forest tent caterpillars (FTCs) induced local and systemic diurnal emissions of (À)-germacrene D, along with (E )-b-ocimene, linalool, (E )-4,8-dimethyl-1,3,7-nonatriene (DMNT), benzene cyanide, and (E,E )-a-farnesene, from leaves of hybrid poplar. FTC feeding induced substantially higher levels of volatiles in local and systemic leaves than did mechanical wounding. A full-length poplar sesquiterpene synthase cDNA (PtdTPS1) was isolated and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
189
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(204 citation statements)
references
References 36 publications
11
189
1
3
Order By: Relevance
“…For example, feeding of forest tent caterpillars (Malacosoma disstria) on P. trichocarpa 3 deltoides resulted in local and systemic emission of a complex volatile blend comprising mainly monoand sesquiterpenes, but also benzyl cyanide (Arimura et al, 2004). Here, we demonstrated that aldoximes and related nitrogen-containing volatiles in P. trichocarpa were only produced and released from herbivore-damaged leaves and not from undamaged neighboring leaves (Figures 6B and 6C; see Supplemental Table 5 online).…”
Section: Nitrogenous Volatiles Are Emitted Exclusively From Damaged Lmentioning
confidence: 71%
“…For example, feeding of forest tent caterpillars (Malacosoma disstria) on P. trichocarpa 3 deltoides resulted in local and systemic emission of a complex volatile blend comprising mainly monoand sesquiterpenes, but also benzyl cyanide (Arimura et al, 2004). Here, we demonstrated that aldoximes and related nitrogen-containing volatiles in P. trichocarpa were only produced and released from herbivore-damaged leaves and not from undamaged neighboring leaves (Figures 6B and 6C; see Supplemental Table 5 online).…”
Section: Nitrogenous Volatiles Are Emitted Exclusively From Damaged Lmentioning
confidence: 71%
“…However, the known grand fir and few loblolly pine TPS genes cannot account for all oleoresin terpenoids in conifers. Nothing is known about TPS genes of induced volatile emissions in conifers , and only a few TPS genes of herbivore-induced terpene emission are known in other angiosperm plants (Shen et al, 2000;Schnee et al, 2002;Fäldt et al, 2003a;Arimura et al, 2004). Species of spruce (Picea spp.…”
mentioning
confidence: 99%
“…Accordingly, tent caterpillars feeding on leaves of hybrid poplar induced local and systemic emissions of (-)-germacrene D, (E)-β-ocimene, linalool, (E)-4,8-dimethyl-1,3,7-nonatriene, benzene cyanide, and (E,E)-α-farnesene (Arimura et al, 2004b). This emission of volatile terpene compounds was correlated with an increase in transcription levels of a sesquiterpene synthase greatly induced in response to herbivory (Arimura et al, 2004a). We found putative Citrus homologs to terpene synthases expressed preferentially in leaves (Figure 4).…”
mentioning
confidence: 92%